2008
DOI: 10.1124/jpet.107.134650
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon Monoxide-Releasing Molecule Tricarbonyldichlororuthenium(II) Dimer Protects Human Osteoarthritic Chondrocytes and Cartilage from the Catabolic Actions of Interleukin-1β

Abstract: We have investigated the effects of a carbon monoxide-releasing molecule, tricarbonyldichlororuthenium(II) dimer (CORM-2), on catabolic processes in human osteoarthritis (OA) cartilage and chondrocytes activated with interleukin-1␤. In these cells, proinflammatory cytokines induce the synthesis of matrix metalloproteinases (MMPs) and aggrecanases, including members of a disintegrin and metalloproteinase with thrombospondin domain (ADAMTS) family, which may contribute to cartilage loss. CORM-2 down-regulated MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Moreover, CO may decrease both ROS and NO production in osteoarthritic chondrocytes stimulated by IL-1β [37]. This was associated to a weak expression of MMP-1, MMP-3, MMP-10 and MMP-13 [42]. In our study, we showed that CO reduces Nox4 activity.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, CO may decrease both ROS and NO production in osteoarthritic chondrocytes stimulated by IL-1β [37]. This was associated to a weak expression of MMP-1, MMP-3, MMP-10 and MMP-13 [42]. In our study, we showed that CO reduces Nox4 activity.…”
Section: Discussionsupporting
confidence: 53%
“…These molecules have been shown to be effective in a wide range of animal models, including pancreatitis, hepatic ischemia-reperfusion, colitis, cutaneous wound healing, neuropathic pain and osteoarthritis [98]. Like NO and H 2 S, CO can suppress leukocyte adherence to the vascular endothelium and reduce pro-inflammatory cytokine expression by inhibiting NF-B [100][101][102][103]. Also in line with the actions of the other two major gaseous mediators, CO has been shown to exert particularly potent protective effects in the GI tract [104].…”
Section: Carbon Monoxidementioning
confidence: 99%
“…Recently, CO-releasing molecules (CO-RMs) have been synthesized as a new drug class able to reproduce many of the biological effects of HO and CO [8], [9]. We have shown previously that CORM-3 exerts anti-arthritic effects in mice [10] and CORM-2 reduces the production of some inflammatory mediators and MMPs in OA chondrocytes [11], [12]. However, evidence to show whether CO-RMs are capable of modulating the metabolism of OA synoviocytes is lacking.…”
Section: Introductionmentioning
confidence: 99%